Problems of research of medieval written monuments (XIII-XV centuries) of religious content in the Mamluk-Kipchak language - Aubakirova , Қ.Қ.; Mustafaeva , А.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
The article examines the degree of study of religious and didactic monuments in the Mamluk-Kipchak language and discusses the research problems of medieval manuscripts. Along with examples of the accepted classification of written monuments in the Kipchak language, the article presents a classification of works in the Mamluk-Kipchak language by content. For the first time, an attempt is made to centralize the well-known Mamluk-Kipchak manuscripts, to give them a brief scientific description, to obtain information on theological monuments, and also to analyze the degree of study. In order to revive the heritage of our ancestors with a thousand-year history, which was forgotten in the context of current globalization, there is a need to re-study the history of the nation through the search, acquisition, and comprehensive study of medieval manuscripts that store information on the history, culture, religions and religious beliefs of our nation. Among the written monuments that are the heritage of the entire Turkic world, religious manuscripts in the Mamluk-Kipchak language of the 13-15th centuries occupy a special place. They are valuable both for Egyptian society and they are a valuable source in the study of the history, culture, language, religion, and beliefs of the Turkic peoples in general.